2020
DOI: 10.21203/rs.3.rs-56380/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of an immune-related gene signature to improve prognosis prediction of colorectal cancer patients

Abstract: Background: Despite recent advance in immune therapy, great heterogeneity exists in colorectal cancer (CRC) patients’ outcome. In this study, we aimed to analyze the Immune-related gene (IRG) expression profiles from two independent public databases and develop an effective signature to forecast patients’ prognosis.Method: IRGs were collected from The Cancer Genome Atlas (TCGA) database to identify a prognostic genes signature, which was verified in Gene Expression Omnibus (GEO) database. Gene function enrichm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…By taking advantage of rapid development of omics sequencing technologies, researchers can investigate the underlying molecular mechanisms of CC progression (27,(37)(38)(39). Moreover, transcriptome profiling of colon tumors provided valuable information for researchers to develop biomarkers-based risk score models to promote the prognosis of CC (12)(13)(14)40,41). The ECM, which can convey specific signals to cells, thereby can regulate several critical processes including immune cell migration, immune cell activation, proliferation, and their differentiation (19,42,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By taking advantage of rapid development of omics sequencing technologies, researchers can investigate the underlying molecular mechanisms of CC progression (27,(37)(38)(39). Moreover, transcriptome profiling of colon tumors provided valuable information for researchers to develop biomarkers-based risk score models to promote the prognosis of CC (12)(13)(14)40,41). The ECM, which can convey specific signals to cells, thereby can regulate several critical processes including immune cell migration, immune cell activation, proliferation, and their differentiation (19,42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is essential to establish novel and robust prognostic biomarker signatures to identify the molecular changes that can reliably estimate clinical outcomes of CC patients, which would have tremendous value of guiding appropriate individualized clinical managements and treatments for CC patients. Much effort has been devoted to determining how the changes of distinct gene signatures such as ferroptosis-related, RNA binding proteins (RBPs)-related, immune-related gene signatures can be utilized to predict CC prognosis recently (12)(13)(14). The extracellular matrix (ECM) is composed of complex network of non-cellular components (CCs) of tissue, including glycoproteins, collagens, and proteoglycans, that provides both essential structural and biomedical supports for its cellular constituents, which can regulate the development and maintain tissue homeostasis (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, recent studies demonstrated that distinct immune gene signatures are prognostically relevant in cancer patients. [19][20][21][22] However, the IRGs selected in most studies are derived from the ImmuPort database or from ssGSEA. In the present study, the 14-IRG signature for sarcoma patients is based on ImmucellAI and WGCNA, which provides a novel and innovative method to identify prognostic biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…angiogenesis and tumor cell migration [24]. IL20RB has been reported as a prognosis-related immune gene for pancreatic cancer [25], lung cancer [26] and colorectal cancer [27]; KLRC2 has also been predicted to play a role among many immune cell subpopulations [28,29]. The current study also demonstrates that IL20RB and KLRC2 affect the infiltration of immune T-cell subsets in renal cancer, which is expected to further explain the mechanism of immune action of IL20RB and KLRC2 in renal cancer.…”
Section: P R E P R I N Tmentioning
confidence: 99%